PENOKOHAN KRSNA DAN BALARĀMA DALAM RELIEF CERITA KRSNA DI CANDI LARA JONGGRANG - Andri Restiyadi (Balai Arkeologi Yogyakarta, 2011)
Kṛṣṇa's Story Relief that carved on Lara Jonggrang Temple is an interesting relief which is rarely glimpsed as an object of research. This relief's depict Kṛṣṇa and Balarāma's life since childhood to adulthood. However, not all of the story is being carved, but the selected parts only. The aim of this research is to know how to characterize of Kṛṣṇa and Balarāma on that relief. This research will use instrinsic story builder approach that usually used in literacy criticism.